Role of Borneol Induced Autophagy in Enhancing Radiosensitivity of Malignant Glioma - Li, Qinglin; Xia, Liang; Sun, Caixing; Zhang, Huangjie; Zheng, Mengying; Zhang, Hongyan; Lu, Hongyang; Wang, Zeng (Frontiers in Oncology, 2021)
Glioma is the common primary craniocerebral malignancy with unfavorable prognosis. It is currently treated by surgical resection supplemented by radiotherapy, although the resistance of glioma cells to radiation limits the therapeutic outcomes. The hypoxic tumor microenvironment plays a key role in the radio-resistance of glioma by blocking autophagy. In the previous study, we found that the natural terpene derivative borneol inhibited the hypoxia-stimulated transcription factor HIF-1α by targeting the autophagy-related mTORC1/eIF4E pathway. The aim of the present study was to determine the potential radiosensitizing effects of borneol and the underlying mechanisms. We found that borneol administration along with radiotherapy significantly inhibited the growth of primary glioma cells in vitro and in vivo. Furthermore, borneol markedly increased the number of autophagosomes in the glioma cells, which coincided with increased expression of beclin-1 and LC3. In addition, silencing mTORC1 and eIF4E upregulated Beclin-1 and LC3 and decreased the expression of HIF-1α, thereby inhibiting tumor cell proliferation. Our findings suggest that borneol sensitizes glioma cells to radiation by inducing autophagy via inhibition of the mTORC1/eIF4E/HIF-1α regulatory axis.